2014
DOI: 10.1172/jci68101
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback between NF-κB and TNF-α promotes leukemia-initiating cell capacity

Abstract: Acute myeloid leukemia (AML) is a heterogeneous hematologic malignancy that originates from leukemia-initiating cells (LICs). The identification of common mechanisms underlying LIC development will be important in establishing broadly effective therapeutics for AML. Constitutive NF-κB pathway activation has been reported in different types of AML; however, the mechanism of NF-κB activation and its importance in leukemia progression are poorly understood. Here, we analyzed myeloid leukemia mouse models to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(194 citation statements)
references
References 60 publications
(59 reference statements)
11
180
2
1
Order By: Relevance
“…4) in relation to elevated NF-κB activation (Fig. 3B) agrees with that NF-κB activation leading to TNF-α production in tumor cells (31,32). NF-κB is a key regulator of MMP-2 and MMP-9 expression (33,34), even in SAS cells (35) Figure 5.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…4) in relation to elevated NF-κB activation (Fig. 3B) agrees with that NF-κB activation leading to TNF-α production in tumor cells (31,32). NF-κB is a key regulator of MMP-2 and MMP-9 expression (33,34), even in SAS cells (35) Figure 5.…”
Section: Discussionsupporting
confidence: 81%
“…This may be an underlying mechanism by which GSAS/N3 and GSAS/N5 cells exert high invasive and metastatic activities. Such a positive feedback between NF-κB and TNF-α was reported in leukemia-initiating cells and contributes to leukemia progression (32). The present study suggests that this mechanism is present in the oral cancer cells and associated with enhanced secretion of active MMPs, augmenting invasion and probably metastasis of the malignant cells.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is well-known that MSCs actively participate in the "angiogenic switch" not only by releasing various angiogenic factors [62], but also by recruiting circulating vascular progenitor cells [63]. MSCs may inhibit adaptive and innate immunity by releasing immunosuppressive cytokines and effectors including tumor necrosis a (TNF-a) and interferon-g (IFN-g) either directly or under the influence of leukemic cells [64][65][66][67]. In addition, under the influence of Axl-expressing leukemic cells, BM derived MSCs are induced to express and produce the Axl ligand, i.e.…”
Section: Aml Cells Remodel the Nichementioning
confidence: 99%
“…IL6, too, might be a suitable and up to date target since high IL-6 levels have been associated with a poor clinical outcome and refractory disease [66] and humanized monoclonal antibodies against the IL-6 receptor are nowadays available. Recently, it has been observed that TNF-a released from stromal cells might be minimal, but this cytokine along with a high proteasome activity is critical for maintaining the constitutive activation of nuclear factor Kb (NFkB) in LICs but not in HSCs and non-LIC fractions of AML cells [67]. Thus, combining the inhibition of NFkB/TNF-a signaling with conventional chemotherapy might be a beneficial treatment strategy.…”
Section: Potential Targetsmentioning
confidence: 99%